2016
DOI: 10.4236/cweee.2016.52007
|View full text |Cite
|
Sign up to set email alerts
|

Geothermal Gradient and Heat Flow in the Nigeria Sector of the Chad Basin, Nigeria

Abstract: Information on geothermal gradient and heat flow within the subsurface is critical in the quest for geothermal energy exploration. In a bid to ascertain the thermal potential of Nigeria sector of the Chad Basin for energy generation, subsurface temperature information from 19 oil wells, 24 water boreholes drilled to depths beyond 100 metres and atmospheric temperature from the Chad basin were utilized in calculating geothermal gradient of the area. Selected ditch cuttings from the wells were subjected to therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 5 publications
2
7
0
Order By: Relevance
“…Citation: Abraham EM, Nkitnam EE (2017) Review of Geothermal Energy Research in Nigeria: The Geoscience Front. Int J Earth Sci Geophys 3:015 face temperature information from 19 oil wells, 24 water boreholes drilled to depths beyond 100 metres and atmospheric temperature from the Chad basin were utilized by Kwaya, et al [40]. Selected ditch cuttings from the wells were subjected to thermal conductivity test using Thermal Conductivity Scanner (TCS) at the Polish Geological Institute Laboratory in Warsaw.…”
Section: Geophysicsmentioning
confidence: 99%
“…Citation: Abraham EM, Nkitnam EE (2017) Review of Geothermal Energy Research in Nigeria: The Geoscience Front. Int J Earth Sci Geophys 3:015 face temperature information from 19 oil wells, 24 water boreholes drilled to depths beyond 100 metres and atmospheric temperature from the Chad basin were utilized by Kwaya, et al [40]. Selected ditch cuttings from the wells were subjected to thermal conductivity test using Thermal Conductivity Scanner (TCS) at the Polish Geological Institute Laboratory in Warsaw.…”
Section: Geophysicsmentioning
confidence: 99%
“…It is a part of the western Central African Rift System (WCAS) that was formed in response to the mechanical separation of the African crustal blocks in the cretaceous (Genik, 1992;Avbovbo et al, 1986;Okosun, 1995;Nwachukwu and Ekine, 2010). This basin lies between latitudes 10 o N to 14 o N and longitudes 12 o E to 15 o E in North-Eastern Nigeria (Kwaya et al, 2016), as indicated in the map of Figures 1. The study area is limited between latitudes 12 o 30' and 12 o 00'E and longitudes 12 o 00' and 13 o 30'N.…”
Section: Geologic Setting Of Study Area Within the Bornu-chad Basinmentioning
confidence: 92%
“…Several authors have studied the geothermal state of the Bornu-Chad basin (Kwaya et al, 2016;Nwankwo et al, 2009;Umar, 1999;Nwankwo and Ekine, 2010;Nwazeapu, 1990;Askira and Schoeneich, 1987;Olugbeniro and Ligous, 1999;Lawal et al, 2018). In this basin, different but close values are reported by different authors.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The Nigerian sector of Chad basin has been identified to have high prospect for geothermal energy [3][4]. But only few works have investigated geothermal parameters in the Nigerian sector of Chad basin [5][6][7][8][9][10][11][12]. In addition, these works used data from oil wells.…”
Section: Introductionmentioning
confidence: 99%